Hanging in Sweetwater - Overholser, Stephen (Doubleday & Co, 1974)
Boomer Jones, a fifteen-year-old runaway, becomes involved in a bloody range war between ruthless ranchers and defenseless homesteaders
40763
Keywords: Western; Runaway